MODEL OF TERAHERTZ PULSE-BLOOD FLOW INTERACTION FOR OVERCOMING CHOLESTEROL PLAQUE VENTURI EFFECT IN ARTERY - Usman Malik; Muhamad Hamdi (Komunikasi Fisika Indonesia, 2015)
This model attempts to analyze involvement using THz radiation interaction with cholesterol depositsform plaque on the inner walls of an artery. It interacts with blood fluid by principle of THz radiation heattransfer mechanism for overcoming cholesterol plaque venture effect in artery. Athermanous plaque, abuildup of white blood cell wherein is sometimes termed fatty, despite absence of adiposities depositswithin the wall of an artery. When cholesterol deposits form plaque on the inner walls of an artery, thevelocity of blood flow increases when t increases and generates higher pressure according to the ventureeffect. Consequences of this effect can lead to collapse the artery, causing a myocardial infarction in acoronary artery. Analysis on the cholesterol plaque effect in blood flow through the forced convection ofterahertz pulse heat release in artery causes the blood flow change after interacting with terahertz pulse.The results indicate that blood velocity and diffusivity for axial positions to higher with change oftemperature rises along radial position caused by heat release of the absorbed terahertz pulse power inblood flow. Transient behavior of a 10 THz pulse-blood flow interaction in artery wherein the resultchosen varies the blood kinematics viscosity to see how fast this final blood velocity profile is attained.Indeed, for very small blood kinematics viscosities, the response is slower. This result is to be expectedsince the blood kinematics viscosity unit is cm2/s just like the diffusion coefficient and the thermaldiffusivity.